Enhancement of Photosynthetic Capacity in Spongy Mesophyll Cells in White Leaves of Actinidia kolomikta - Yu, Miao; Chen, Li; Liu, Dong-huan; Sun, Dan; Shi, Guang-li; Yin, Yan; Wen, De-quan; Wang, Zhen-xing; Ai, Jun (Frontiers in Plant Science, 2022)
Considering that Actinidia kolomikta bears abundant white leaves on reproductive branches during blossoming, we hypothesized that the white leaves may maintain photosynthetic capacity by adjustments of leaf anatomy and physiological regulation, thereby providing sufficient photoassimilates to the flowers. To test this hypothesis, leaf anatomy, gas exchange, chlorophyll a fluorescence and the transcriptome were examined in white leaves of A. kolomikta during flowering. The palisade and spongy mesophyll in the white leaves were thicker than those in green ones. Chloroplast development in palisade parenchyma of white leaves was abnormal, whereas spongy parenchyma of white leaves contained functional chloroplasts. The highest photosynthetic rate of white leaves was ~82% of that of green leaves over the course of the day, and stem girdling between the white leaves and flowers resulted in stagnation of flower development. In addition, the maximum quantum yield of PSII (Fv/Fm) of the palisade mesophyll in white leaves was significantly lower than those of green ones, whereas Fv/Fm and quantum yield for electron transport were significantly higher in the spongy mesophyll of white leaves. Photosynthetic capacity regulation of white leaf also was attributed to up-regulation or down-regulation of some key genes involving in photosynthesis. Particularly, up-regulation of sucrose phosphate synthase (SPS), glyeraldehyde-3-phosphate dehydrogenase (GAPDH) and RuBisCO activase (RCA) in white leaf suggested that they might be involved in regulation of sugar synthesis and Rubisco activase in maintaining photosynthetic capacity of white leaf. Conclusions: white leaves contained a thicker mesophyll layer and higher photosynthetic activity in spongy parenchyma cells than those of palisade parenchyma cells. This may compensate for the lowered photosynthetic capacity of the palisade mesophyll. Consequently, white leaves maintain a relatively high photosynthetic capacity in the field.